Prevalence of Domestic Violence and Associated Factors among Women During Ante-natal Check-up at Medical College: A cross-sectional study - Chaudhary, Khusboo; Rajbhandary, Sudipta Bhakta; Bhaskar , Ravi Kumar; Yadav, Binod Kumar (Med Phoenix, 2025)
Introduction: Domestic abuse, also known as domestic violence or intimate partner violence, is a pattern of behavior used to gain or maintain control over an intimate partner. According to the World Health Organization (WHO), one in three women may experience domestic abuse in their lifetime. The study examined the existing prevalence of all forms of domestic violence and its associated factors. Materials and Methods: This analytical cross-sectional study was conducted at the antenatal clinic of the National Medical College Teaching Hospital. Participants were selected using a random sampling method where lottery method was further used. With pregnant women assigned to interview days based on their outpatient department serial numbers. Results: More than half (55.4%) of the respondents experienced domestic violence during their lifetime. Psychological violence (52.1%) was the most common form, followed by physical (41.9%) and sexual violence (28.4%). Socio-demographic factors such as lack of education, absence of property ownership, unemployment, early marriage (10-15 years), and arranged marriage were significantly associated with domestic violence (p<0.05). The primary perpetrators were husbands (68.5%), followed by mothers-in-law (29.8%). Conclusion: The prevalence of domestic violence has increased enormously. The findings emphasize the need for targeted interventions, including education, economic empowerment, and legal measures, to prevent domestic violence and protect vulnerable women.